Clinical Validation of Automated Corrected QT-Interval Measurements From a Single Lead Electrocardiogram Using a Novel Smartwatch - Mannhart, Diego; Hennings, Elisa; Lischer, Mirko; Vernier, Claudius; Du Fay de Lavallaz, Jeanne; Knecht, Sven; Schaer, Beat; Osswald, Stefan; Kühne, Michael; Sticherling, Christian; Badertscher, Patrick (Frontiers in Cardiovascular Medicine, 2022)
Introduction: The Withings Scanwatch (Withings SA, Issy les Moulineaux, France) offers automated analysis of the QTc. We aimed to compare automated QTc-measurements using a single lead ECG of a novel smartwatch (Withings Scanwatch, SW-ECG) with manual-measured QTc from a nearly simultaneously recorded 12-lead ECG. Methods: We enrolled consecutive patients referred to a tertiary hospital for cardiac workup in a prospective, observational study. The QT-interval of the 12-lead ECG was manually interpreted by two blinded, independent cardiologists through the tangent-method. Bazett’s formula was used to calculate QTc. Results were compared using the Bland-Altman method. Results: 317 patients (48% female, mean age 63 ± 17 years) were enrolled. HR-, QRS- and QT-intervals were automatically calculated by the SW in 295 (93%), 249 (79%) and 177 patients (56%), respectively. Diagnostic accuracy of SW-ECG for detection of QTc-intervals ≥ 460ms (women) and ≥ 440ms (men) as quantified by the area under the curve was 0.91 and 0.89. The Bland-Altman analysis resulted in a bias of 6.6ms (95% limit of agreement (LoA) –59ms to 72ms) comparing automated QTc-measurements (SW-ECG) with manual QTc-measurement (12-lead ECG). In 12 patients (6.9%) the difference between the two measurements was greater than the LoA. Conclusion: In this clinical validation of a direct-to-consumer smartwatch we found fair to good agreement between automated-SW-ECG QTc-measurements and manual 12-lead-QTc measurements. The SW-ECG was able to automatically calculate QTc-intervals in one half of all assessed patients. Our work shows, that the automated algorithm of the SW-ECG needs improvement to be useful in a clinical setting.